Presentation and management of Chronic Suppurative Otitis Media at Lady Reading Hospital, Peshawar (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the clinical and operative findings of the patients sustaining chronic suppurative otitis media. Patients and Methods: This descriptive cross sectional study of six months duration was conducted at the department of ENT, Head and Neck Surgery, Hayat Medical Complex (HMC), Peshawar-Pakistan from June 2012 to December 2012. All the patients of any age and either gender having discharging ears for more than three months were included. Those patients having aural discharge due to otitis externa or trauma were excluded from study. All patients having otogenic intracranial complications were first treated by neurosurgeon before treating the primary focus in ears. Mastoid surgery was performed according to the nature and type of disease. Results: A total of 93 patients were enrolled who were 67 male and 26 females with male to female ratio of 2.5:1. These patients were in age range from 5 years to 67 years with mean age of 37+13 years. Most of the patients were from lower socioeconomic group (56%). In this study 90 patients (96.78%) had atticoantral type tympanic perforation while 3 patients (3.22%) presented with tubotympanic type tympanic perforation with commonest presentation of ear discharge (100%).In majority of patients (54.71%) there was mild to moderate hearing loss. In 36 patients (38.7%) total perforation was common among atticoantral type while cholesteatoma was the commonest (47.31%) finding in this disease. Conclusion: Otorrhoea is the common presentation of atticoantral type diseased ear that is best treated with mastoidectomy operation to minimize its complications.
Keywords: Perforation, Myringoplasty, Mastoidectomy, Otogenic complication